Type of Cosurfactant Effects on Particle Size in Nanoemulsion Drug Delivery Systems - Ike Widyaningrum; Efriza Fahmi Triyoga; Nugroho Wibisono; Shinta Kusumawati; Anita Puspa Widiyana (East Asian Journal of Multidisciplinary Research, 2023)
Nanoemulsions are thermodynamically or kinetically stable compared to conventional emulsions, and the particle size of nanoemulsions is around 5-200 nm. Until now, there has been no research comparing propylene glycol and PEG 400 cosurfactants for nanoemulsions, so it needs to be investigated. Laboratory experimental research with cosurfactant propylene glycol and PEG 400 Formula 1 and Formula 2 were repeated three times (n = 3) for each nanoemulsion formula. Parameters of physical properties (organoleptic, viscosity, particle size, index polydispersity) and chemical properties (pH). Evaluated and analyzed, <0.05 is considered significant. The results of formula 1 and formula 2 obtained the same clear organoleptic properties. The average particle size with cosurfactant propylene glycol was 10.41 ± 0.14 nm and PEG 400 was 12.32 ± 0.38 nm (p <0.05). The average viscosity, polydispersity index, and pH of propylene glycol were 8.72 ± 1.12; 0.03±0.02; 4.20 ± 0.04; and PEG 11.26 ± 1.80; 0.39 ± 0.58; 4.03±0.03. This shows that the type of cosurfactant has an effect on the size of the nanoemulsion particles.